Preservers for the p-Norm of Linear Combinations of Positive Operators - Gergő Nagy (Abstract and Applied Analysis)
We describe the structure of those transformations on certain sets of positive operators which preserve the p-norm of linear combinations with given nonzero real coefficients. These sets are the collection of all positive pth Schatten-class operators and the set of its normalized elements. The results of the work generalize, extend, and unify several former theorems.